Traditional embroidery symbolism as a means of forming authorial style in contemporary women’s costume - Олійник , Г. М.; Струмінська, Т. В.; Мамченко, Я. О.; Навольська, Л. В.; Фролов , І. В.; Ременєва, Т. В. (Fashion Industry, 2026)
Purpose. To study the ornamental and symbolic system of Ukrainian embroidery as a cultural code and to identify the possibilities of its authorial reinterpretation in contemporary women’s costume. Methods. The research employs visual-analytical and information-based analysis of Ukrainian embroidery, as well as methods of systemic and comparative analysis, and artistic and design modelling for the development of a creative women’s clothing collection. Results. The features of embroidery as a “cryptogram” technique have been identified, in which ornaments and symbols serve as a cultural code. An authorial scheme for encoding the word “NEZLAMNA” (“UNBREAKABLE”) based on the “Brody Script” by V. Pidhirniak has been proposed. A women’s clothing collection using authorial embroidery has been developed, combining ethnic motifs with current fashion trends. The collection was presented at the international competition “Pecherski Kashtany – 2025.” Scientific novelty. The integration of the concept of an “embroidered cryptogram” into contemporary clothing design is proposed through the adaptation of V. Pidhirniak’s symbolic alphabet. The potential of Ukrainian embroidery as a means of visual communication in fashion design is explored. Practical significance. The conducted research on Ukrainian embroidery as a linguistic and symbolic system provides a foundation for creating contemporary collections in the light industry sector. The developed creative sketches and women’s clothing collection demonstrate the possibility of innovative use of Ukrainian embroidery in modern fashion. The research results may be applied in designers’ practice aimed at promoting national heritage.